School management strategies in implementing textile waste-based craft learning - Ermayani, Ermayani; Budiwirman, Budiwirman (Universitas Jambi, Indonesia, 2026)
This study examined school management strategies in implementing textile waste-based craft learning at MAN 1 Pekanbaru as part of sustainable education and creative economy development. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving school leaders, teachers, and students. The findings reveal that successful implementation was supported by strategic curriculum integration, instructional leadership, resource optimization, and collaborative program planning. The school adopted sustainability-oriented learning policies that encouraged environmental awareness, creativity, and entrepreneurial skills among students. Effective coordination between school management and teachers enabled the integration of textile waste utilization into arts education while aligning with institutional goals. The study highlights that school leadership plays a central role in fostering innovative, environmentally responsible learning practices. These findings contribute to the discourse on sustainability leadership and school-based management in promoting environmentally responsive educational programs.